Penerapan Strategi E-Commerce Untuk Meningkatkan Penjualan Pada Butik Rasyaf Collection Dengan Metode Market Basket Analysis - Yahya, Yahya -; Novianti, Eva; Syamsiyah, Nur; Panjaitan, Muhammad Martian Ardiansyah (Jurnal Sains & Teknologi Fakultas Teknik Universitas Darma Persada, 2024)
Rasyaf Collection Clothing Store offers a wide variety of women's clothing, including dresses, pants, accessories, shoes, jackets, and more. Currently, Rasyaf Collection Boutique's marketing system relies on social media platforms like Facebook, WhatsApp, and Instagram. However, the boutique owner has not yet implemented effective marketing strategies, making it difficult to reach customers, as they have to visit the boutique in person to purchase clothing, which limits the marketing reach. One of the challenges hindering the development of this business is the lack of product information available to potential customers, such as difficulties in identifying the types of products being sold and managing product inventory. The development of this system implements a prototyping model and is carried out in stages or linearly. It involves analyzing customer behavior from specific groups using market analysis methods. When specific patterns are unknown, market basket analysis is typically used as a starting point to gather information about transaction data. Data sources for market basket analysis include credit card transactions, discount coupons, lottery tickets, and customer complaint calls. The results of this research indicate that the developed e-commerce website application can assist the boutique owner in selling various types of clothing and managing product inventory. Additionally, this application will make it easier for customers to access information about the products being sold and allow them to choose clothing from Rasyaf Collection Boutique.